COGNITIVE PERSPECTIVES ON MYSTICAL REALISM IN BRITISH AND UZBEK PROSE (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This paper investigates mystical realism in British and Uzbek prose through the lens of cognitive literary studies. It argues that mystical realism represents an intensified mode of consciousness, where narrative structures simulate spiritual perception and ethical insight. By analyzing selected texts, the study demonstrates how authors construct symbolic frameworks, blend mental spaces, and guide readers’ cognitive engagement with transcendental experience. Drawing on cognitive poetics, conceptual metaphor theory, and mental space blending, the paper highlights shared mechanisms across cultural traditions, while revealing differences in ethical orientation and symbolic representation. The study underscores the value of cognitive approaches for understanding cross-cultural literary expressions of mysticism and consciousness.